SIMPLIFY: 2x+3y-z-{x+3y-[y+2z-(x-2y-4z)]}
- print Print
- list Cite
Expert Answers
Luca B.
| Certified Educator
calendarEducator since 2011
write5,348 answers
starTop subjects are Math, Science, and Business
You need to open the brackets moving from inside to outside such that:
`2x+3y-z-{x+3y-[y+2z-(x-2y-4z)]} = 2x+3y-z-[x+3y-(y+2z-x+2y+4z)]`
`2x+3y-z-[x+3y-(y+2z-x+2y+4z)] = 2x+3y-z-(x+3y-y-2z+x-2y-4z)` `2x+3y-z-(x+3y-y-2z+x-2y-4z) = 2x+3y-z-x-3y+y+2z-x+2y+4z`
Notice that minus sign in front of brackets changes the sign of each term inside brackets when you open the brackets.
You need to collect like terms such that:
`(2x - x - x) + (3y- 3y + y + 2y) + (-z + 2z + 4z)`
`0 + 3y + 5z`
Hence, simplifying the algebraic expression yields `2x+3y-z-{x+3y-[y+2z-(x-2y-4z)]} = 3y + 5z.`
Related Questions
- Solve the system: x+2y -z=3 2x-y+2z=8 x+y+z=3
- 1 Educator Answer
- Solve the equations: x + y + z = 0 2x + 2y + 2z = 0 -x + 3y + 4z = 2
- 1 Educator Answer
- Solve for x, y and z, given the following equations: x + y + z = 6 2x - y + 3z = 9 -x + 2y + 2z = 9
- 1 Educator Answer
- 2x-3y = 8 x+2y=3 solve x and y
- 1 Educator Answer
- How do you solve these equations? x+y+2z=5 x+2y+z=8 2x+3y-z=1
- 1 Educator Answer